Crooked Hills - Bunn, Cullen (Crystal Lake, IL : Earwig Press, 2011)
Brothers Charlie and Alex find adventure when they take an unexpected trip to visit their Aunt Mary in the haunted town of Crooked Hills.
Cover title: Cullen Bunn's Crooked Hills.
4.8
3-6.
3-6
Keywords: Brothers -- Juvenile fiction; Adventure and adventurers -- Fiction; Brothers -- Fiction; Ghosts -- Fiction; Adventure fiction; Brothers -- Fiction; Ghost stories; Adventure fiction; Ghost stories